An Analysis Of English-Indonesian Translation In Novel"Memoirs Of A Geisha" By Arthur Golden Into "Memoirs Of A Geisha: Memoar Seorang Geisha" By Listiana Srisanti - Oktavia, Restumardi (2004)
This research is intended to clarify the addition and subtraction on the translation of book novel Memoir of a Geisha into Memoir of a Geisha: Memoar Seorang Geisha. The type of data is qualitative data. The source of the research data are both novels Memoirs of a Geisha as the source language and Memoirs of a Geisha: Memoar Seorang Geisha as the target language text. In taking the data, she uses documentation. She begins by finding the sentences or groups of sentences which contain the case of addition and subtraction, classifying the cases, and counting the percentage of those type to find the dominant classification. Besides, the writer analyzes the equivalent message in translation process. If the message can be transferred well, it includes in equivalent message although happened addition and subtraction. The result of the research shows that from 150 data 60 belongs to addition process and 90 data includes subtraction process. From 60 data, there are 7 kinds of addition namely: filling out elliptical expression 1 datum (1,67%), obligatory specification 24 data (40%), required by grammatical 4 data (6,66%), amplification from implicit into explicit status 5 data (8,33%), classifier 1 datum (1,67%), connectives 7 data (11,6%), and categories of the receptor language 19 data (31,67%). Related to 90 data of subtraction there are 6 kinds, namely: repetition 3 data (3,33%), specification of reference 10 data (11,11%), conjunction 7 data (7,78%), transitional 10 data (11,11%), categories 10 data (11,11%), amplification from explicit to implicit status 49 data (54,44%). There are 146 data (97,33%) belonging equivalent message and 4 data (2,67%), belonging to non equivalent. Finally, the writer concludes that the novel Memoir of a Geisha and its translation is well and under-stable.